Free space optical communication based on a multi-wavelength optical phased array using Fresnel reflection - Eisuke Haraguchi; Hitomi Ono; Takahiro Suzuki; Tomohiro Akiyama; Akihiro Fujie; Yuta Takemoto; Toshiyuki Ando (Applied Physics Express)
We report a coherent laser transmitter for free space optical communications based on multiwavelength coherent beam combining. We performed 5.6 Gbps free-space optical communications using a two-element optical phased array with three wavelengths combined. As a result, we demonstrated that there is no degradation in communication performance due to inter-element optical phase locking in the optical phased array.